Errors of Punctuation Transfer In English Compositions by English Learners Academic Year (2013) English Department in FKIP UHN Pematangsiantar - Bertaria Sohnata Hutauruk (Journal of English Language and Culture, 2017)
This research analyzes the errors made by the English learners of academic year (2013) at FKIP UHN Pematangsiantar in using punctuation marks in writing. Punctuation is a large part of a system of conventions in which the function is to assist the written language in indicating those elements of speech which cannot be conveniently set down on paper: chiefly pause, pitch, and stress. From the background of this research, the writer formulated a question as a problem, that is: what are the types of interference errors of punctuations found in the English compositions made by English learners of the academic year (2013) semester V at English Department in FKIP UHN Pematangsiantar? To discuss the problem, the writer uses theories of Markwardt (1990), Ritter (2002), Edward (2001), Swan (1980), Marcella Frank (1972), and Tregidgo (1949). Norrish (1983:7) says that error is a systematic deviation from the accepted system of the target language. Punctuation exists to clarify meanings in the written word (Ritter, 2002:113). The lack of punctuation is likely to cause great strain for the reader and lower marks for the students. In the methodology, the writer uses qualitative research to solve the problem, which is focused on the process. In getting data, the writer explains about punctuation marks and their usage. After that the writer makes a test to know whether the students understand the explanation or not. The writer gives a text without punctuation. Here, the writer will find out the errors made by the students and make the correct one. The writer found that the common errors made by the students are the use of capitalization and quotation marks. It is followed by the use of full stop, comma, question marks and the last is quotation mark. There are forty students’ writings used as the subject of the research. Keywords: errors, punctuation, English composition